Transformasi digital dalam mencapai keberlanjutan di bidang ekonomi - Izza, Olivia Maghfitrotul (Maliki Interdisciplinary Journal, 2024)
Digital transformation has become key to achieving sustainability in economics and finance, changing the way we interact with markets, resources and the environment. This article discusses the role of digital transformation in accelerating the achievement of sustainability goals in economics and finance, highlighting its positive impact on efficiency, inclusion and innovation. In an economic context, digital transformation enables more efficient technology adoption, expands market access, and creates sustainable business models. With digital platforms, e-commerce and financial technology, business people can reduce operational costs, increase supply chain efficiency and reach a wider market globally. In the financial sector, digital transformation plays a key role in increasing financial inclusion, access to financial services and transparency. Through technology-based financial services such as digital banking and electronic payments, individuals and businesses around the world can access previously unaffordable financial services. However, challenges such as the digital divide, data security and regulatory uncertainty still need to be overcome. It is important for governments, regulators and other stakeholders to work together to create an enabling environment for sustainable and inclusive digital transformation. By understanding the complexity of digital transformation and taking appropriate steps, we can optimize its potential to achieve economic development uncertainty still need to be overcome. It is important for governments, regulators and other stakeholders to work together to create an enabling environment for sustainable and inclusive digital transformation. By understanding the complexity of digital transformation and taking appropriate steps, we can optimize its potential to achieve economic development.